ENGLISH TEACHERS’ READINESS IN DESIGNING LESSON PLAN BASED ON CURRICULUM MERDEKA AT VOCATIONAL SCHOOL NUMBER 1 JAMBI - Azizah, kharisma Nur (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This research, conducted by Kharisma Nur Azizah, explores the readiness of English teachers at SMKN 1 Kota Jambi in designing lesson plans based on the